Semantic Priming between Verbal and Pictorial Code in the Visual Modality - Rebernjak, Blaž (2008)
Assuming that concepts can be activated by both pictures and words, and that the activation can spread to neighboring concepts, we tried to demonstrate experimentally the effects of semantic priming between verbal and pictorial codes of visual modality. The reduction of reaction time to pictures and words that were preceded by semantically related words and pictures, respectively, was evident. The next step is to reduce the overall reaction time so that conscious contamination can be kept at a minimum by adopting a lexical decision paradigm and applying it to pictorial material.
Projekt MZOS
ENG